2015
DOI: 10.11113/jt.v78.4489
|View full text |Cite
|
Sign up to set email alerts
|

Improving Environmental Impact Assessment (Eia) Process in Malaysia

Abstract: Environmental Impact Assessment (EIA) is a planning tool to identify, predict and evaluate potential environmental impacts and mitigation measures in the early stages of proposed projects. Although EIA has been implemented in Malaysia for over 25 years, the EIA practices have yet to achieve the parameters of effective environmental management and sustainable development. Hence, this research aims to improve the EIA process in Malaysia. Three objectives were utilised in this research which are to recognise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…According to Makmor and Ismail (2014), the public participation carried out under the First Schedule for EIA in Malaysia is often shallow and insignificant. Briffet et al (2004), Harun & Mazlan (2008), Makmor and Ismail (2016a), Marzuki (2009) and Li et al (2012) have concurred with evidences that shown most of the EIA reports of the First Schedule activities that were submitted and approved by the DOE without public participation. As for the Second Schedule activities, it is mandatory to administer the public participation under the EIA guidelines.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…According to Makmor and Ismail (2014), the public participation carried out under the First Schedule for EIA in Malaysia is often shallow and insignificant. Briffet et al (2004), Harun & Mazlan (2008), Makmor and Ismail (2016a), Marzuki (2009) and Li et al (2012) have concurred with evidences that shown most of the EIA reports of the First Schedule activities that were submitted and approved by the DOE without public participation. As for the Second Schedule activities, it is mandatory to administer the public participation under the EIA guidelines.…”
Section: Introductionmentioning
confidence: 64%
“…Conclusively, the EIA is interpreted as a sophisticated management tool that identifies, evaluates and mitigates effects from prior to the development in the proposal stage, ensuring the development is sustainable and environmental friendly.The increase of economic growth in Malaysia has pressured the Government to implement a new order to establish balance the vast economic growth to the environmental protection in Malaysia (Mustafa, 2011). Hence, the Environmental Quality Act (EQA) was enacted in 1974 to avoid, minimise and regulate the level of pollution thus sustain the Malaysian environment (Makmor and Ismail, 2016a;Memon, 2000;Mustafa, 2011;Rahman et al, 2001). The Environment Impact Assessment was inaugurated in Malaysia in 1975 after the enactment of the Environment Quality Act (EQA) in 1974 (Makmor and Ismail, 2016a;Memon, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Companies A and D, the authorities keep adding onto the requirements while the study is in progress, thereby delaying the completion of the assessment by the consultants. Issues in the EIA process are also noted by Makmor and Ismail (2015), namely they observed that the Department of Environment (DOE) officers are generalists and not specialists, and they, therefore, have limited knowledge on the scope of EIA. This probably explains the changes in the specifications during the study and thereby resulting in higher costs for companies in producing the EIA.…”
Section: Arbitrary Behaviour and Lack Of Competent Officialsmentioning
confidence: 99%
“…EIA is a tool used to identify the environmental, social and economic impacts of a project before decision-making. EIA is a planning tool to identify, predict and evaluate potential environmental impacts and mitigation measures in the early stages of proposed projects [9].…”
Section: Environmental Impact Assessment (Eia) Processmentioning
confidence: 99%